ANALISIS PENILAIAN KELAYAKAN USAHA WARUNG AYAM BAKAR MBA NANA DI SUKARAJA NUBAN - Erlina Anggraini; M Fahrul Hidayat (CV. Denasya Smart Publisher, 2026)
The study assesses the feasibilityof warung ayam bakar mba nana using a descriptive qualitative approach based on interviews with the owner, field observations an literature review from 2014-2024. The Business demonstrates promising financial potential with affordable prices and a broad market. Environmentally, proper waste and fuel management is essential for sustainability. From an environmental aspect, the warung needs to manage waste and fuel properly to ensure it is environmentally friendly. The technical aspect indicates adequate facilities with attention to cleanliness and ventilation for customer comfort. However, the business is currently not legally feasible as it lacks a valid business license, so it is recommended to complete the legal requirements promptly to support the sustainability and credibility of the business.